Melanesians and Music on the Move: South Sea Island Shipboard and Plantation Performance in Queensland, 1860s–1906. Issue 4 (2nd October 2017) - Webb, Michael; Webb-Gannon, Camellia
ABSTRACT: Taking a historical ethnomusicological approach, this article argues that shipboard and plantation music and dance practices cast new light on the ways South Sea Islanders (SSI) acted out agency and asserted new identities as they became tangled up in the dynamics of colonial encounters. Trading ships started to operate in Melanesia in the 1840s and island men were quickly attracted to the nautical life. Contact with the West brought opportunity but also exploitation when in 1863 the recruitment of Islanders for farm and plantation work in Queensland began. As they ventured into the unknown on recruiting ships, Islanders engaged in performance in order to establish cross-societal bonds with villagers from islands other than their own, and also with European sailors and settlers. Experimenting with any and all modes of sound making, SSI looked to music as a source of enjoyment and a means of individual and collective self-advancement. They took instruments, repertoire items, and gramophones back to their home islands as evidence of their familiarity with the wider world, and as creative resources to employ in the changing times ahead of them. Those who remained in Queensland at the beginning of the 20th century faced the challenge of how to integrate and indigenize the new musical ideas, and transform them into life – and community-sustaining expressions.